Force-velocity profile during vertical jump cannot be assessed using only bodyweight jump and isometric maximal voluntary contraction tasks - Sarabon, N.; Kozinc, Z.; Markovic, G. (Scientific Reports, 2020)
Recently, the two-point method of force-velocity (F-V) profiling of multi-joint human movements has been introduced and validated. In this study, we investigated the validity of estimating the jumping F-V profile using only bodyweight jump and isometric maximal voluntary contraction (MVC) task. Participants (n?=?30) performed 3 repetitions of squat (SJ) and counter-movement jumps (CMJ), each at loads that were progressively increased by 10 kg increments, with the number of loads depending on the individual`s ability. Then, 3 isometric MVC trials were performed in 3 knee angles (30°, 60° and 90°). F-V profiling of SJ and CMJ were performed using the multiple-point method, the two-point method, and the novel Jump-MVC method. The results showed poor to fair validity of the novel Jump-MVC method for assessing jumping F-V profile (most ICC < 0.5, most CV > 10%, significant systematic bias present, and the presence of proportional bias). The exception was the estimation of theoretical maximal power, which was highly valid for both SJ and CMJ (ICC = 0.91-0.95; CV = 5.0-6.3%). In contrast, validity of the two-point method was excellent (all ICC > 0.90; CV = 2-6%). Although additional studies are needed, present results suggest that the F-V profiling of vertical jumps should be performed using the two-point method with distal loads.